2018
DOI: 10.3390/atmos9050188
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Precipitation Events in Serbia: Defining the Threshold Criteria for Emergency Preparedness

Abstract: Abstract:Considering recent weather events in Serbia (especially the floods in 2014), a need has arisen for research that would help in identifying extreme weather phenomena. Therefore, the aim of this paper is to determine the thresholds above which intense precipitation can be considered as extreme precipitation events in Serbia. In this study, we determined the frequency of precipitation occurring at an intensity above the threshold of an extreme phenomenon , as well as the frequency of precipitation occurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…In the 21st century, the erosion rate is expected to increase due to global warming and anthropogenic activities, such as land use and land cover changes (LULCC), which are associated with a more powerful hydrological cycle characterized by a higher magnitude of rainfall and more frequent occurrences of heavy rainfalls [70]. The analysis of rainfall and extremes in Serbia has shown that the frequency of heavy rainfall has generally increased [71]. The annual amount of precipitation has not changed significantly, but the pluviometric regime has changed, which can have a significant impact on the vegetation.…”
Section: Discussionmentioning
confidence: 99%
“…In the 21st century, the erosion rate is expected to increase due to global warming and anthropogenic activities, such as land use and land cover changes (LULCC), which are associated with a more powerful hydrological cycle characterized by a higher magnitude of rainfall and more frequent occurrences of heavy rainfalls [70]. The analysis of rainfall and extremes in Serbia has shown that the frequency of heavy rainfall has generally increased [71]. The annual amount of precipitation has not changed significantly, but the pluviometric regime has changed, which can have a significant impact on the vegetation.…”
Section: Discussionmentioning
confidence: 99%
“…Differences among locations, more pronounced in May than in March, were also related to convective precipitation and its highly diverse spatial distribution [35]. Extreme values of RMSE in 2014 at numerous locations were the result of excessive precipitation (50% of the meteorological stations registered exceeded thresholds for extreme precipitation) in that year in Serbia [36] (Supplementary Material 3). Noticed seasonality and variation in the calculated parameters from March to May might be related to the impact of plant development on orchard micrometeorological conditions and air temperature variation in the height of fruit tree crowns, where air temperature sensors are typically installed.…”
Section: Hres Outputsmentioning
confidence: 99%
“…Differences among locations, more pronounced in May than in March, were also related to convective precipitation and its highly diverse spatial distribution [35]. Extreme values of RMSE in 2014 at numerous locations were the result of excessive precipitation (50% of the meteorological stations registered exceeded thresholds for extreme precipitation) in that year in Serbia [36] (Supplementary Material 3).…”
Section: Hres Outputsmentioning
confidence: 99%
“…Climate change is a reality, and this is evidenced by many studies that have confirmed temperature changes and changes in precipitation patterns (Burić, Ducić, & Mihajlović, 2018;Mahmoudi, Mohammadi, & Daneshmand, 2019;Ruml et al, 2017). In Serbia, it was determined that the frequency of precipitation is at the intensity above the extreme occurrence level and the frequency of precipitation is at or above the absolute daily maximum during the reference period (Anđelković et al, 2018). Besides that, Malinović-Milićević et al (2018) determined that the climate of the northern and central parts of Vojvodina is getting wetter in terms of the precipitation magnitude and frequency, reflecting the characteristics of the central European regime.…”
Section: Introductionmentioning
confidence: 99%